The matching rule of Panum’s limiting case and its influencing factors - Shi, Yuyu; He, Ziyi; Deng, Yuzhen; Li, Huayun (Frontiers in Psychology, 2023)
Panum’s limiting case is one of the typical configurations of monocular occlusion region. The matching rule of Panum’s limiting case is the key to understanding how monocular occlusion region produces stereopsis. There were some controversies about the matching rule of Panum’s limiting case, for example, uniqueness constraint and double matching. This paper further discusses its matching mechanism on the basis of previous studies. In Experiment 1, fixation position was adopted to present the stimulus in a short time to explore the matching rules in Panum’s limiting case. We assume that when stimuli are presented in a short period of time, the reported result that a single feature in one eye may be matched alternately with two features in the other eye. This matching rule is called “fast alternative matching” in this article. In Experiment 2, we further investigated the effect of fixation position on Panum’s limiting case matching results. The results show that the matching rule of Panum’s limiting case is alternating matching, and the position of the fixation could affect the matching result of participants.